HEMIBOS (BOVINI, BOVIDAE, MAMMALIA) FROM THE PINJOR FORMATION OF PAKISTAN - M. A. Khan; M. Iqbal; M. Akhtar (Journal of Animal and Plant Sciences, 2009)
The dental material of Hemibos from the Plio-Pleistocene of the Pinjor Formation (2.6 – 0.6 Ma) in the Upper Siwaliks (Pakistan) is reported here. The new specimens consist of two fragmentary maxillae. The comparative morphological and matric study of Hemibos dental fossils provide interesting information about individual variation.
Keywords: Hemibos; Bovine; Pinjor Formation; Upper Siwaliks; Plio-Pleistocene